2009
DOI: 10.4049/jimmunol.0802888
|View full text |Cite
|
Sign up to set email alerts
|

STIM1-Independent T Cell Development and Effector Function In Vivo

Abstract: Store-operated Ca2؉ entry (SOCE) is believed to be of pivotal importance in T cell physiology. To test this hypothesis, we generated mice constitutively lacking the SOCE-regulating Ca 2؉ sensor stromal interaction molecule 1 (STIM1). In vitro analyses showed that SOCE and Ag receptor complex-triggered Ca 2؉ flux into STIM1-deficient T cells is virtually abolished. In vivo, STIM1-deficient mice developed a lymphoproliferative disease despite normal thymic T cell maturation and normal frequencies of CD4 ؉ Foxp3؉… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
121
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(140 citation statements)
references
References 44 publications
18
121
1
Order By: Relevance
“…The closely related STIM2 has been shown to regulate basal cytosolic and store Ca 2+ concentrations in different cell types (13). The recent generation of mice lacking STIM molecules in T cells confirmed the essential function of STIM1 for SOCE (12,14) and also revealed the contribution of STIM2 to this process (15). The significance of SOCE for T cell function in vivo, however, has not been definitively addressed to date despite the recent description of human immunodeficiency syndromes associated with deficiencies in STIM1 function (16).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…The closely related STIM2 has been shown to regulate basal cytosolic and store Ca 2+ concentrations in different cell types (13). The recent generation of mice lacking STIM molecules in T cells confirmed the essential function of STIM1 for SOCE (12,14) and also revealed the contribution of STIM2 to this process (15). The significance of SOCE for T cell function in vivo, however, has not been definitively addressed to date despite the recent description of human immunodeficiency syndromes associated with deficiencies in STIM1 function (16).…”
mentioning
confidence: 77%
“…The significance of SOCE for T cell function in vivo, however, has not been definitively addressed to date despite the recent description of human immunodeficiency syndromes associated with deficiencies in STIM1 function (16). A first study has revealed that STIM1-deficient T cells display defects in homeostatic T cell proliferation but, despite abolished SOCE, are able to support humoral immune responses after vaccination and can induce acute graft-versus-host disease following adoptive transfer into allogeneic hosts (12). In contrast, the significance of STIM-dependent SOCE for inflammatory reactions in vivo has remained elusive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…S8A). nTreg can be activated and expanded by superagonistic CD28-specific mAb (CD28SA; D665) in mice (24,25). Injecting CD28SA into mice with Treg-specific inactivation of NFAT2 (Nfat2 fl/fl × FIC; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…T cell-dependent antibody responses and graft vs. host disease response appear relatively unaffected in STIM1 2/2 mice (Beyersdorf et al 2009). Partial function of B cells is also evident in STIM1-or Orai1-deficient patients who develop lymphoproliferative disease and an autoimmune attack on their own neutrophils and thrombocytes Picard et al 2009).…”
Section: Immune Cellsmentioning
confidence: 99%